Risk factors for the development of bronchopulmonary pathology in workers producing synthetic polyacrylonitrile fiber - Raikova, S. V.; Komleva, N. E.; Starshov, A. M.; Mazilov, S. I.; Novikova, T. A. (Sibirskiĭ nauchnyĭ medit︠s︡inskiĭ zhurnal, 2022)
Aim of the study was to assess the risk of bronchopulmonary pathology in workers of the production of synthetic polyacrylonitrile fiber as a result of exposure to harmful chemicals and smoking tobacco products. Material and methods. During the periodic medical examination, the function of external respiration and adherence to smoking in 137 employees were studied, medical records were analyzed (025/u accounting form). Hygienic assessment of working conditions was carried out on the basis of the results of in-situ sanitary and hygienic studies. Results and discussions. As a result of a hygienic assessment of working conditions, it was found that workers engaged in the production of polyacrylonitrile fiber are subject to the combined intermittent effects of harmful chemicals of hazard classes 1–3 (acrylonitrile, methyl acrylate, hydrocyanide, ammonia, sodium rhodanide, sulfuric acid, methanol, isopropyl alcohol, ethylene glycol), the content of which in the working area exceeded the maximum permissible concentrations in 1.6% of samples. The occupational risk of developing bronchopulmonary diseases in groups of workers who smoke is assessed as unacceptably high, while in people exposed to harmful chemicals, its level is 28.46 times higher than in people who are not exposed to these effects. The risk of the formation of ventilation disorders in groups of smoking workers is unacceptably high, while its level is 2.46 times higher in workers exposed to harmful chemicals than in non-workers in such conditions. In groups of workers exposed to harmful chemicals, the occupational risk of obstructive disorders is unacceptably high, in the group of smokers the risk is 2.32 times higher. Conclusions. Among the employees of the enterprise producing synthetic polyacrylonitrile fiber, the influence of tobacco smoking on the development of bronchopulmonary pathology is higher than the influence of harmful working conditions, and the use of smoking tobacco products significantly increases the negative effect of chemical pollutants.